Analisis Yuridis Dispensasi Perkawinan Terhadap Pengaruh Pelaksanaan Batas Usia Perkawinan Pasca Revisi Undang-Undang N0. 16 Tahun 2019 - Zaharnika, R. Febrina Andarina; Erlina, Erlina; Putri, Anggelin Ardina Dwi (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2026)
Child marriage in Indonesia remains a complex issue despite the revision of Law Number 1 of 1974 through Law Number 16 of 2019, which sets the minimum age for marriage at 19 years for both men and women. However, the existence of a marriage dispensation mechanism granted by the court remains a factor that allows underage marriage to occur. This study aims to analyze the legal basis of marriage dispensation and its impact on the effectiveness of the implementation of the marriage age limit. The research method used is normative legal research with a statutory and conceptual approach. The results show that marriage dispensation remains a legal loophole that affects the effective implementation of Law Number 16 of 2019. Therefore, it is necessary to strengthen regulations and supervision in granting marriage dispensation to protect children's rights.